Adhesion of hematopoietic progenitor cells to human mesenchymal stem cells as a model for cell−cell interaction - Wagner, Wolfgang; Wein, Frederik; Roderburg, Christoph; Saffrich, Rainer; Lammert, Anne; Krause, Ulf; Schubert, Mario; Benes, Vladimir; Eckstein, Volker; Maul, Holger; Ho, Anthony Dick (Experimental hematology, 2007)
Objective - The significant role of direct contact between hematopoietic progenitor cells (HPC) and the cellular microenvironment for maintaining “stemness” has been demonstrated. Human mesenchymal stem cell (MSC) feeder layers represent a surrogate model for this interaction. Specific adhesion molecules are responsible for this cell−cell contact. - Methods - To define cell−cell contact between HPC and MSC, we have studied adhesive interaction of various fractions of HPC by using a novel assay based on gravitational force upon inversion. Adherent and nonadherent cells were separated and further analyzed with regard to gene expression and long-term hematopoietic culture initiating cell (LTC-IC) frequency. - Results - HPC subsets with higher self-renewing capacity demonstrated significantly higher adherence to human MSC (CD34+ vs CD34−, CD34+/CD38− vs CD34+/CD38+, slow dividing fraction vs fast dividing fraction). LTC-IC frequency was significantly higher in the adherent fraction than in the nonadherent fraction. Furthermore, genes coding for adhesion proteins and extracellular matrix were higher expressed in the adherent subsets of CD34+ cells (fibronectin 1, cadherin 11, vascular cell adhesion molecule-1, connexin 43, integrin β-like 1, and TGFBI). - Conclusion - In this study we have demonstrated that primitive subsets of HPC have higher affinity to human MSC. The essential role of specific junction proteins for stabilization of cell−cell contact is indicated by their significant higher expression.